Biometry, Adiposity and Mechanism of Protein Sparing Growth in Congenic Preobese LA/Ntul//-cp rats - Tulp, Orien L (British Journal of Healthcare and Medical Research, 2023)
The LA/Ntul//-cp rat is a congenic rat strain where the obese characteristic is expressed as an autosomal recessive epigenetic trait by 5 to 6 weeks of age in 25% of the offspring of heterozygous breeding pairs. Groups of lean and preobese 6-week-old female rats were subjected to measures of biometry and adipose tissue mass and cellularity of primary adipose tissue depots, followed by measures of in vitro protein synthesis and degradation in auricular appendage (AA) and skeletal digitorum longus muscle (DLM). Adipose depot mass, cell lipid content and tissue cell number were already greater in the dorsal subcutaneous, abdominal retroperitoneal and gonadal depots at 6 weeks of age. The interscapular brown fat depot (IBAT) mass and IBAT mass: body weight was also greater in the obese than the lean littermates. The tissue weights of the heart of obese > lean, but DLM of obese was similar to the lean rats. In contrast, the rates of protein synthesis and degradation as determined by the rate of 14C-phe incorporation into AA and tyrosine degradation from DLM were greater in the lean than the obese, indicating an economy of the energy costs of protein turnover in the obese phenotype. At 4 high energy phosphate bonds per peptide bond formed, protein synthesis represents one of the most biochemically expensive processes of energy metabolism, especially during the active stages of early growth and development of an animal. Thus, the conservation in energy expenditure resulting from an improved efficiency of protein turnover in the obese phenotype is likely a contributing factor in the energy efficiency previously reported in the obese phenotype of this strain of rat and is likely linked to hormonal resistance factors that impact on the efficiency of energy metabolism and a propensity for energy deposition and early onset fat accretion.